(untitled) (The Research of Medical Science Review, 2024)
Purpose: The purpose of this study to analyze the knowledge of participants with CKD on maintenance hemodialysis related to anemia and their quality of life and to implement an educational intervention regarding disease and complication management and to evaluate its effect so the further recommendations can be suggested to decrease the burden of complications. Method: This study was conducted by using the one group pretest –posttest Qusai experimental study design between July2024- Aug 2024 with the sample size of 34. Permission was taken from the institutional review board and informed consent was taken from the participants before the pretest. Randomization done by the third party not aware of objectives and study question. Educational interventions developed from the National Kidney Foundation and KIDGO Clinical practice guidelines were given according to the language feasibility of the participants in three phases. Result: Participants were suffering from anemia and with decrease quality of life due to multiple factors and after educational intervention participant had increase score in their posttest which indicated significant difference in pretest and posttest. Conclusion: Significant improvement in posttest indicated that participants with hemodialysis should be monitored for quality of life and interventions will be effected to increase awareness regarding the complications of hemodialysis in CKD patients.